Geothermal potential of Foreland Basins: A case study from the Western Canadian Sedimentary Basin. (November 2018) - Banks, Jonathan; Harris, Nicholas B.
Highlights: Oil and Gas data is used to locate and map geothermal resources in a sedimentary basin. Power production potential is estimated using volumetric methods. Results of are distilled to specific power output per km 3 of reservoir volume. Flow rates require per unit power are calculated. Overall results are extrapolated to assess the global potential of sedimentary basins as geothermal resources. Abstract: Geotechnical and hydrogeological data from well bore logs and rock cores were used to identify, map, and model the power production potential of geothermal reservoirs in sedimentary formations in the Western Canadian Sedimentary Basin across several municipal districts in western Alberta. We show a general workflow for using oil and gas data to assess geothermal resources in sedimentary basins, present a series of contour maps and stratigraphic grids of salient geothermal reservoir properties and assess the power production potential of these resources using a volumetric (heat-in place) method. In total, throughout the study area, we identified a potential thermal power capacity of ∼6100 MWt per for a 30-year production period. Reservoir depths ranged from about 2500 m to over 5000 m. Formation temperatures ranged from ∼60 °C to over 150 °C. The calculated thermal power capacity equates to ∼1150 MWe of potential electrical power capacity over the 30 year production period, of which ∼ 800 MWe are considered high grade (>120 °C) resources that may reliably produce electricity with existing technology.